Prenatal and Neonatal MR Imaging Findings in Oral-Facial-Digital Syndrome Type VI - Poretti, A.; Brehmer, U.; Scheer, I.; Bernet, V.; Boltshauser, E. (American Journal of Neuroradiology, 2008)
SUMMARY: We report prenatal and neonatal neuroimaging findings in a case of oral-facial-digital syndrome type VI (OFDS VI). Prenatal MR imaging at 29 weeks' gestation showed hypoplastic cerebellar vermis and hemispheres, the molar tooth sign, and a hypothalamic hamartoma. Neonatal MR imaging confirmed these findings. The neonate developed breathing abnormalities and exhibited frontal bossing, multiple bucco-alveolar frenula, and postaxial hexadactyly of both hands. If the molar tooth sign and a hypothalamic hamartoma are present, prenatal diagnosis of OFDS VI is possible.